Bioacoustic monitoring of animal vocal behavior for conservation. Issue 8 (11th June 2019) - Teixeira, Daniella; Maron, Martine; van Rensburg, Berndt J.
Abstract: The popularity of bioacoustics for threatened species monitoring has surged. Large volumes of acoustic data can be collected autonomously and remotely with minimal human effort. The approach is commonly used to detect cryptic species and, more recently, to estimate abundance or density. However, the potential for conservation‐relevant information to be derived from acoustic signatures associated with particular behavior is less well‐exploited. Animal vocal behavior can reveal important information about critical life history events. In this study, we argue that the overlap of the disciplines of bioacoustics, vocal communication, and conservation behavior—thus, "acoustic conservation behavior"—has much to offer threatened species monitoring. In particular, vocalizations can serve as indicators of behavioral states and contexts that provide insight into populations as it relates to their conservation. We explore the information available from monitoring species' vocalizations that relate to reproduction and recruitment, alarm and defense, and social behavior, and how this information could translate into potential conservation benefits. While there are still challenges to processing acoustic data, we conclude that acoustic conservation behavior may improve threatened species monitoring where vocalizations reveal behaviors that are informative for management and decision‐making.